SEISMICITY CRITERIA FOR THE REAL-TIME IDENTIFICATION OF FORESHOCKS IN THE CORINTH GULF - Orfanogiannaki, K.; Papadopoulos, G. A. (Bulletin of the Geological Society of Greece, 2004)
In the Corinth Gulf foreshock sequences occur as a rule within a time interval no longer than four months before the mainshock. If these precursory phenomena could be detected, then it would be utilized for the prediction of the mainshock. However, frequent swarms also characterize the Gulf of Corinth. Therefore, in a real time evaluation, the discrimination between swarms and foreshock sequences is of crucial importance. In this study we focus on establishing seismicity criteria to achieve such discrimination.